2002
DOI: 10.1506/equa-nvj9-e712-ukbj
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Ownership and the Extent to which Stock Prices Reflect Future Earnings*

Abstract: Articles in the financial press suggest that institutional investors are overly focused on current profitability, which suggests that as institutional ownership increases, stock prices reflect less current period information that is predictive of future period earnings. On the other hand, institutional investors are often characterized in academic research as sophisticated investors and sophisticated investors should be better able to use current-period information to predict future earnings compared with othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
145
0
17

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(183 citation statements)
references
References 27 publications
19
145
0
17
Order By: Relevance
“…7 Contemporaneous ERC is often estimated as the sum of the coefficients on current and lagged earnings, b 0 + b 1 . 8 Other recent papers using the informativeness measure are Durnev, Morck, Yeung, and Zarowin (2003), Ayres and Freeman (2001), Jiambalvo, Rajgopal, and Venkatachalam (2002), and Piotroski and Roulstone (2004). 9 There are a number of reasons why management may chose not to capitalize development expenditures which meet the five criteria outlined in SSAP #13.…”
Section: Notesmentioning
confidence: 99%
“…7 Contemporaneous ERC is often estimated as the sum of the coefficients on current and lagged earnings, b 0 + b 1 . 8 Other recent papers using the informativeness measure are Durnev, Morck, Yeung, and Zarowin (2003), Ayres and Freeman (2001), Jiambalvo, Rajgopal, and Venkatachalam (2002), and Piotroski and Roulstone (2004). 9 There are a number of reasons why management may chose not to capitalize development expenditures which meet the five criteria outlined in SSAP #13.…”
Section: Notesmentioning
confidence: 99%
“…On the contrary, abnormal accruals should be affected by the ability and incentives of managers to manipulate earnings and are likely to depend on the efficiency of corporate governance mechanisms. Indeed, literature shows that earnings management can be reduced by outside directors (Peasnell et al, 2001), the auditing committee of the board of directors (Klein, 2002), institutional investors (Jiambalvo et al, 2002) or the active role of inside shareholders (Delgado, 2003). This is the approach of our paper since we try to analyze the relation between the discretionary behaviour of directors and two mechanisms of corporate governance such as capital and ownership structure.…”
Section: Managers' Discretionary Behaviour Earnings Management Corpmentioning
confidence: 99%
“…Moreover, the results also suggested that the stock prices of large firms anticipate information that affects the entire industry, so their returns can anticipate a portion of the small firms' returns. Jiambalvo, Rajgopal and Venkatachalam (2002) and Ayers and Freeman (2003) found a positive association between the institutional ownership percentage in firms' ownership structures and the prices lead earnings phenomenon. For Jiambalvo, Rajgopal and Venkatachalam (2002), this association occurs because institutional investors are more sophisticated and have advantages in acquiring and processing information that are only reflected in future earnings, which would impose lower informational synchronization as these investors' ownership increases.…”
Section: Theoretical Frameworkmentioning
confidence: 95%
“…Jiambalvo, Rajgopal and Venkatachalam (2002) and Ayers and Freeman (2003) found a positive association between the institutional ownership percentage in firms' ownership structures and the prices lead earnings phenomenon. For Jiambalvo, Rajgopal and Venkatachalam (2002), this association occurs because institutional investors are more sophisticated and have advantages in acquiring and processing information that are only reflected in future earnings, which would impose lower informational synchronization as these investors' ownership increases. Ayers and Freeman (2003) also evaluated the influence of analyst coverage on the degree of anticipation of future earnings displayed in stock prices.…”
Section: Theoretical Frameworkmentioning
confidence: 95%
See 1 more Smart Citation